Answer:
2(x - 2)(x - 3).
2x^2 - 10x + 12.
Step-by-step explanation:
Degree 2 means that the highest degree is 2 and we may write it as:
ax^2 + bx + c where a, b and c are constants to be found.
As p(0) = 12, the first 2 terms in the above are zero so c = 12.
The zeros are 2, 3 so we may write it as
a(x - 2)(x - 3) = 0
The last term in the expansion is 12 so:
a*(-2)*(-3) = 12
thus a = 12/6 = 2.
In factored form our polynomial is:
2(x - 2)(x - 3).
Standard form:
2(x - 2)(x - 3)
= 2(x^2 - 5x + 6)
= 2x^2 - 10x + 12.